Response to Stimulations Inducing Circadian Rhythm in Human Induced Pluripotent Stem Cells - Hitomi Kaneko; Taku Kaitsuka; Kazuhito Tomizawa (Cells, 2020)
Regenerative medicine and disease modeling are expanding rapidly, through the development of human-induced pluripotent stem cells (hiPSCs). Many exogeneous supplements are often used for the directed differentiation of hiPSCs to specific lineages, such as chemicals and hormones. Some of these are known to synchronize the circadian clock, like forskolin (Frk) and dexamethasone (Dex); however, the response to these stimulations has not been fully elucidated for hiPSCs. In this study, we examined the response of clock genes to synchronizing stimulation, and compared it with fully differentiated cells, U2OS, and fibroblasts. The expression of clock genes did not show circadian rhythms in hiPSCs with Frk and Dex, which could be due to the significantly low levels of BMAL1. On the other hand, a circadian-like rhythm of D-box binding protein (DBP) expression was observed in hiPSCs by culturing them in an environment with a simulated body temperature. However, the inhibition of temperature-inducible factors, which are involved in temperature rhythm-induced synchronization, could not repress the expression of such rhythms, while the inhibition of HIF-1α significantly repressed them. In summary, we suggest that clock genes do not respond to the synchronizing agents in hiPSCs; instead, a unique circadian-like rhythm is induced by the temperature rhythm.